Molecular and functional characterization of a new non-hemorrhagic metalloprotease from Bothrops jararacussu snake venom with antiplatelet activity - Marcussi, Silvana; BernardeS, Carolina P.; Santos-Filho, Norival A.; Mazzi, Mauricio V.; Oliveira, Clayton Z.; Izidoro, Luiz Fernando M.; Fuly, Andre L.; Magro, Angelo J. [UNESP]; Braz, Antonio S. K. [UNESP]; Fontes, Marcos R. M.; Giglio, Jose R.; Soares, Andreimar M. (Elsevier B.V., 2007)
BjussuMP-II is an acidic low molecular weight metalloprotease (Mr similar to 24,000 and pI similar to 6.5), isolated from Bothrops jararacussu snake venom. The chromatographic profile in RP-HPLC and its N-terminal sequence confirmed its high purity level. Its complete cDNA was obtained by RT-PCR and the 615 bp codified for a mature protein of 205 amino acid residues. The multiple alignment of its deduced amino acid sequence and those of other snake venom metalloproteases showed a high structural similarity, mainly among class P-I proteases. The molecular modeling analysis of BjussuMP-II showed also conserved structural features with other SVMPs. BjussuMP-II did not induce hemorrhage, myotoxicity and lethality, but displayed dose-dependent proteolytic activity on fibrinogen, collagen, fibrin, casein and gelatin, keeping stable at different pHs, temperatures and presence of several divalent ions. BjussuMP-II did not show any clotting or anticoagulant activity on human citrated plasma, in contrast to its inhibitory effects on platelet aggregation. The aspects broached, in this work, provide data on the relationship between structure and function, in order to better understand the effects elicited by snake venom metalloproteases. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: metalloprotease; fibrinogenase; snake venom; Bothrops jararacussu; biological activity; antiplatelet activity; cDNA; molecular model